Far field : digital culture, climate change, and the poles - Marsching, Jane D.; Polli, Andrea (Intellect, 2012)
"Far Field" will be a visually appealing book with numerous rich colour images. It offers cutting edge ideas - a new way to think about the issues surrounding climate change. There is inclusion of fascinating first person accounts of projects at the Poles. "Far Field" is a collection of essays in contemporary cultural studies combined with interview and diary excerpts exploring some of the most significant artistic, scientific, technological and philosophical interpretations of the Poles over the past decade.